2010
DOI: 10.1186/1471-230x-10-142
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic opening of the common bile duct and duodenal stenosis: an overlooked association

Abstract: BackgroundEctopic opening of the common bile duct into the duodenal bulb (EO-CBD-DB) is a rare disease that may be complicated by duodenal ulcer, deformity, stenosis and biliary stones. The aim of this study is to report clinical presentations, endoscopic diagnosis and treatment of this entity as well as to investigate its association with duodenal stenosis.MethodsGastroduodenoscopic findings and radiological imaging were evaluated for ectopic papilla and duodenal stenosis. Diagnostic methods, endoscopic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Bile reflux into the duodenal bulb causes an increase in pH. At high pH, bile acids may cause gastric and duodenal bulb mucosal damage [ 7 , 8 , 11 , 12 , 15 ]. Previous reports also suggest that bicarbonate in pancreatic secretion contributes to the increase in the pH in the bulb, leading to recurrent duodenal ulcer and deformity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile reflux into the duodenal bulb causes an increase in pH. At high pH, bile acids may cause gastric and duodenal bulb mucosal damage [ 7 , 8 , 11 , 12 , 15 ]. Previous reports also suggest that bicarbonate in pancreatic secretion contributes to the increase in the pH in the bulb, leading to recurrent duodenal ulcer and deformity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…At high pH, bile acids may cause gastric and duodenal bulb mucosal damage [ 7 , 8 , 11 , 12 , 15 ]. Previous reports also suggest that bicarbonate in pancreatic secretion contributes to the increase in the pH in the bulb, leading to recurrent duodenal ulcer and deformity [ 12 ]. The presence of pancreatic secretion, in addition to bile, seems to be necessary for the development of deformity, ulcers, and stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is reported that 50-95% of cases with ectopic biliary drainage are seen in the male sex. This might bring to mind an etiologic relation with Y chromosome-induced embryonic abnormality (1,3,7,8) . In our series, male gender dominance was present in support of the findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic opening of the CBD is commonly associated with biliary tract diseases. Gallstone, choledocholithiasis, obstructive jaundice, cholangitis, pancreatitis and peptic ulcer are complications of ectopic CBD openings (1,2,7,8) . Malfunction of the valve mechanism is blamed for the occurrence of these complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation